Combination gemcitabine and PD-L1xCD3 bispecific T cell engager (BiTE) enhances T lymphocyte cytotoxicity against cholangiocarcinoma cells - Methi Wathikthinnakon; Piriya Luangwattananun; Nunghathai Sawasdee; Chutipa Chiawpanit; Vannajan Sanghiran Lee; Piyarat Nimmanpipug; Yingmanee Tragoolpua; Siriphorn Rotarayanont; Thanich Sangsuwannukul; Nattaporn Phanthaphol; Yupanun Wutti-in; Chalermchai Somboonpatarakun; et al. (Scientific Reports)
Abstract Cholangiocarcinoma (CCA) is a lethal cancer with rapid progression and poor survival. Novel and more effective therapies than those currently available are, therefore, urgently needed. Our research group previously reported the combination of gemcitabine and cytotoxic T lymphocytes to be more effective than single-agent treatment for the elimination of CCA cells. However, gemcitabine treatment of CCA cells upregulates the expression of an immune checkpoint protein (programmed death-ligand 1 [PD-L1]) that consequently inhibits the cytotoxicity of T lymphocytes. To overcome this challenge and take advantage of PD-L1 upregulation upon gemcitabine treatment, we generated recombinant PD-L1xCD3 bispecific T cell engagers (BiTEs) to simultaneously block PD-1/PD-L1 signaling and recruit T lymphocytes to eliminate CCA cells. Two recombinant PD-L1xCD3 BiTEs (mBiTE and sBiTE contain anti-PD-L1 scFv region from atezolizumab and from a published sequence, respectively) were able to specifically bind to both CD3 on T lymphocytes, and to PD-L1 overexpressed after gemcitabine treatment on CCA (KKU213A, KKU055, and KKU100) cells. mBiTE and sBiTE significantly enhanced T lymphocyte cytotoxicity against CCA cells, especially after gemcitabine treatment, and their magnitudes of cytotoxicity were positively associated with the levels of PD-L1 expression. Our findings suggest combination gemcitabine and PD-L1xCD3 BiTE as a potential alternative therapy for CCA.